EMPATHY AND THE SCENES OF SPEECHES IN THE WRITINGS OF ANTÔNIO FRANCISCO MELLO, PE. MELLO - de Lima Pacheco, Marcio; Chagas Ramos, Rawy (Revista Gênero e Interdisciplinaridade, 2024)
This article investigates the trajectory and intellectual legacy of Father Antônio Francisco de Mello, highlighting empathy in his speeches and his contributions to the historical and social context. Born in 1863, Mello addressed themes such as social justice and moral responsibility, encouraging ethical self-reflection. The analysis of his poems reveals three degrees of empathy: the experience of another person, the explanation that attributes meaning, and the objectification of the experience. The concept of ethos, based on Aristotle’s Rhetoric, is central to the construction of the orator’s image. The article also explores the discursive ethos according to Dominique Maingueneau, emphasizing the interaction between the ethos shown and said, in addition to the pre-discursive ethos. The research proposes a psychoanalytic analysis of the elements that influence the relationship between speaker and recipient.